2021
DOI: 10.1175/jas-d-20-0025.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry Signatures of an Equatorially Symmetric Matsuno–Gill Circulation Pattern

Abstract: Matsuno-Gill circulations have been widely studied in tropical meteorology, but their impact on stratospheric chemistry has seldom been explicitly evaluated. This study demonstrates that, in a model nudged to reanalysis, anticyclonic Rossby wave gyres that form near the tropopause due to equatorially-symmetric heating in the troposphere provide a dynamical mechanism to influence tropical and subtropical atmospheric chemistry during near-equinox months. The anticyclonic flow entrains extratropical air from high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Finally, the Matsuno–Gill model has been applied recently in the study of stratospheric chemistry (Wilka et al. 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Matsuno–Gill model has been applied recently in the study of stratospheric chemistry (Wilka et al. 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Matsuno-Gill model was also used as a prototype model for studying the weak temperature gradient approximation, where it was shown that under this approximation, the Rossby wave part of the response is not trapped equatorially, and the model has a far-field response to a localized tropical heating (Bretherton & Sobel 2003). Finally, the Matsuno-Gill model has been applied recently in the study of stratospheric chemistry (Wilka et al 2021).…”
Section: Introductionmentioning
confidence: 99%